Gis Application in Spatial Analysis of Crime in a Developing Nation: A Case of Ogbomoso, Nigeria - Oyenike, Adigun Folasade; Odedare, K.O.; Olajoke, Abolade; Olateju, IGE James (Advances in Social Sciences Research Journal, 2016)
Against the background of astronomical rise in crime rate, the increasing and dynamic sophistication in the strategies employed by criminals and the inability of the Nigerian Criminal Justice System to analyze this social malady with improve technology, the study explored the application of Geographic Information System in the spatial analysis of crime in Ogbomoso South Local Government Area. Within the context of residential densities, police crime records from 1999 to 2003 were analyzed. The geometric data were captured from the township map of the study area. Information from 240 questionnaire administered formed the supplementary data used as the socioeconomic attributes of respondents. The analyses were carried out using ArcView 3.2a and Statistical Package for Social Scientist (SSPS) packages. Spatial analyses such as spatial search, buffering and overlay were done. The study revealed that there is a marked variation in the distribution of crime between and within residential areas. Five hot spots of crime were identified. Further observation was made on areas that may not be sufficiently covered when there is a distress call due to inadequate number of police post or station which is a major security infrastructure that signifies the presence of Government Crime Control Personnel. With this observation the study suggests provision of more police post in areas that are not covered. The study posits that Nigeria Police Authority should be equipped with adequate training and technology in order to enhance a wholesome control of crime within the context of the world’s dynamic technologies. This will be effective if other activities within the urban environment are coordinated in order to reduce criminal opportunities.